Pengembangan Realistik Sebagai Pilihan dalam Peningkatkan Pemahaman Konsep Pengujian Hipotesis - Susie Harini (IQTISHODUNA: Jurnal Ekonomi Islam, 2015)
By identifying those problems of development, the researcher was eager to develop model, which was able to improve students’ understanding concept toward the material about testing the hypothesis. In addition, this model should be able to develop students’ participation in develop activities. One of the teaching develop models that can help students in understanding the concept of testing the hypothesis is Realistic develop.